2012
DOI: 10.4174/jkss.2012.83.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intraoperative parathyroid hormone monitoring to predict success of parathyroidectomy for secondary hyperparathyroidism

Abstract: Purpose In secondary hyperparathyroidism (sHPT), it is unclear which criterion for intraoperative parathyroid hormone (ioPTH) decline performs best and whether ioPTH monitoring is sufficiently efficacious in predicting postoperative surgical cure by retrospective review. Methods In 80 parathyroidectomies for sHPT, patients with ioPTH monitoring and follow-up PTH assay were categorized into physiologically accepted and failed groups. Receiver operating characteristic (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…These efforts are not commonly used. It is known that intraoperative iPTH monitoring is a good predictor of a successful parathyroidectomy in secondary hyperparathyroidism [10]. In our case, we knew that immediate parathyroidectomy had failed though intraoperative iPTH monitoring and frozen biopsy.…”
Section: Discussionmentioning
confidence: 73%
“…These efforts are not commonly used. It is known that intraoperative iPTH monitoring is a good predictor of a successful parathyroidectomy in secondary hyperparathyroidism [10]. In our case, we knew that immediate parathyroidectomy had failed though intraoperative iPTH monitoring and frozen biopsy.…”
Section: Discussionmentioning
confidence: 73%
“…En nuestros pacientes, una caída de PTHop ≥ 75% del valor basal, predijo curación en 98% y en 100% de los casos de HPT 2° e HPT 3° respectivamente. Sin embargo, con la evidencia actualmente disponible, no existe consenso sobre el nivel de descenso de PTHop asociado a éxito de la cirugía ni a predicción de curación posterior en pacientes con HPT renal [8][9][10][11] .…”
Section: Discussionunclassified
“…En el caso del HPT 3°, la cirugía es el tratamiento de elección 4 . La medición de PTH intraoperatoria (PTHop), método ampliamente validado en la cirugía de pacientes con HPT primario, está menos estudiada en este tipo de pacientes [8][9][10][11] . Nuestro objetivo primario fue evaluar la presentación clínica y resultados del tratamiento quirúrgico de los pacientes con HPT 2° y terciario operados en nuestra institución.…”
unclassified
“…Gasparri et al [60] found iPTH to be a useful adjunct to MIBI and parathyroid weight in these patients by helping the surgeon to know that no ectopic tissue is present (i.e., if after removing four glands, iPTH remains elevated, the surgeon should search for an additional gland). Kim et al [21] recommend an 85 % decline from baseline at 40 min post-subtotal thyroidectomy for the best prediction of cure, while Sharma et al [61] advocate a near-total parathyroidectomy, leaving a vascularized remnant of one gland that approximates the size of two normal parathyroid glands and aims for an absolute final iPTH level of 100 pg/mL.…”
Section: Secondary or Tertiary Hyperparathyroidismmentioning
confidence: 99%
“…Others conclude that when MIBI alone localizes a single adenoma, iPTH does not add value [18]. Still others argue in favor of routine bilateral exploration [19,20], and others have explored its use in secondary and tertiary hyperparathyroidism [21,22].…”
Section: Introductionmentioning
confidence: 99%